Its perfect where you have left it
Simplify and you will get ur answer
LHS = 1/6 (k+1) [k(6k^2+14k+7) + 6(2k+3)^2)
= 1/6 (k+1) [6k^3+14k^2+7k+6(4k^2+12k+9)]
= 1/6 (k+1) [6k^3+14k^2+7k+24k^2+72k+54]
= 1/6 (k+1) [6k^3+38k^2+79k+54]
Now see if you can get (k+2) out of [6k^3+38k^2+79k+54] using
polynomial factorization method ....
Code: _____________________
2 | 6 38 79 54
| -12 -54 -54
--------------------------
| 6 26 27 00
YES u could ....
so (k+2) (6k^2+26k+27) = [6k^3+38k^2+79k+54]
Now see if you can get represent (6k^2+26k+27) in terms of (k+1)
6k^2+26k+27 = 6(k+1)^2+14(k+1)+7
So finally
LHS = ((k+1)(k+2)[6(k+1)^2+14(k+1)+7])/6
You are done!